Middle Age Like Fight or Modern Symbiosis?; Comment on "Substitutes or Complements? Diagnosis and Treatment With Non-conventional and Conventional Medicine" - Michael Frass (Kerman University of Medical Sciences, 2015)
Complementary and alternative medicine (CAM) is widely used by patients worldwide. Financial factors may influence the decision to use CAM. National Health Systems are requested to consider CAM in their health plans.